2022
DOI: 10.3390/healthcare10010079
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Late Miscarriage and Practical Implications for Post-Natal Health Care: Qualitative Study

Abstract: Miscarriage is the most common reason for pregnancy loss, affecting around one in four pregnancies. It is classified as a traumatic event, associated with an increased risk for depression, anxiety, post-traumatic stress, alcohol dependence, somatic symptoms, sexual dysfunction, suicide, and complicated grief. This study aimed to analyse experiences of late miscarriage and to describe practical implications for post-natal health care based on characteristics of pregnancy loss revealed in a qualitative study. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…This aspect has been analyzed in another related qualitative research on late miscarriage experiences in a Lithuanian sample. Thematic analysis has described women’s reactions to late miscarriage: the Initial splitting state (Dissociation, An Opened Void, An impaired Symbiosis, and The Body is Still Pregnant while the Psyche is Mourning); Betrayal of the body (Symbolic Experience of Internalized Death, Shocking Materiality of the Ongoing Miscarriage, Lost control of the Body, and Confusing Body Signals); Disconnecting (Depersonalizing Medical Environment, Guilt Falsifies perception, and Retreat as a means of Self-Preservation); and Reconnecting (Collecting Shatters and Reinterpretation of Maternal Identity) [ 27 ]. The study mentioned has also revealed that the ability to accept one’s body and the birth of children, as well as the experience of motherhood, were important factors for successful coping after miscarriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect has been analyzed in another related qualitative research on late miscarriage experiences in a Lithuanian sample. Thematic analysis has described women’s reactions to late miscarriage: the Initial splitting state (Dissociation, An Opened Void, An impaired Symbiosis, and The Body is Still Pregnant while the Psyche is Mourning); Betrayal of the body (Symbolic Experience of Internalized Death, Shocking Materiality of the Ongoing Miscarriage, Lost control of the Body, and Confusing Body Signals); Disconnecting (Depersonalizing Medical Environment, Guilt Falsifies perception, and Retreat as a means of Self-Preservation); and Reconnecting (Collecting Shatters and Reinterpretation of Maternal Identity) [ 27 ]. The study mentioned has also revealed that the ability to accept one’s body and the birth of children, as well as the experience of motherhood, were important factors for successful coping after miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative study was implemented in order to validate the qualitative findings of the first project’s stage. A part of the results of the qualitative interview analysis was presented in the previous publication [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…This aspect of perinatal loss for women transcends Fuchs’ view of grief as bodily experience [6], since the event has an immediate physical impact, regardless of emotional distress. The dissociative symptoms that this experience ensues are also well characterized in Kukkiene and Zemaitiene’s study [13], highlighting the primary stage of loss as a splitting state described as an “ impaired symbiosis between a mother and the fetus, between the old and the emerging identity of a pregnant woman, and between the body and the psyche .” Here also, Golan and Leichtentritt’s study [14] dissects the feeling of ambiguity found in the participants. It is discussed that ambiguity, a central theme of any loss (just as proposed by Fuchs [6]), is felt as an uncertainty deriving from self-disenfranchising grief, which is further intensified by external invalidation [14].…”
Section: Phenomenological Approach To the Experience Of Grief In Repr...mentioning
confidence: 89%
“…The process of sharing the news with family and friends sometimes enhances feelings of shame and guilt, as most women at some point blamed themselves for the loss [7, 8, 13, 15, 19]. In fact, Adolfsson et al [7] found “guilt and emptiness” to be the major theme of women’s experience following miscarriage, which was taken as a personal failure and an embarrassment, and women ended up directing their anger toward themselves, feeling responsible for the miscarriage because of being negligent (while unaware of the consequences), namely, allowing stress or anxiety, smoking, drinking alcohol, lifting heavy things, their own thoughts, or “not wanting the child enough.” Perhaps due to the reduction of guilt, women were able to find some relief when the cause was found [8, 15], though cause is commonly unexplained [2, 23].…”
Section: Phenomenological Approach To the Experience Of Grief In Repr...mentioning
confidence: 99%
“…For women that undergo EPL, hospitalization, pain, the sole sight of blood, fetal tissue, the fetus, or even the subjective perception that a baby is dying inside the womb can be traumatic enough for the appearance of PTSD symptoms ( 24 , 40 ). Recent studies suggest that around 10–45% of these women show symptoms of post-traumatic stress disorder ( 39 , 41 ). Regarding its persistence in time, an early study by Engelhard et al ( 42 ), reported that symptoms of PTSD were visible in 25% of their sample at the 1-month mark, and had substantially decreased by the 4-month mark.…”
Section: Introductionmentioning
confidence: 99%